Developing a National Interdisciplinary Educational Framework for Professionals Working with Children in the Early Years : Final Report. - Grant, Julian; Gregoric, Carolyn; Sumsion, Jennifer; Brinkman, Sally; Walsh, Kerryann; Jovanovic, Jessie; Parry, Yvonne; Miller, Keith; Colmer, Kaye; Gibson, Christine (Dept of Education and Training, Australia, 2017)
The first five years of a child's life are irrefutably important, establishing life-long health, social and economic outcomes. To optimise these outcomes, national and state policy is directing professionals from a range of disciplinary backgrounds involved with children to work more collaboratively than ever before. As pre-service education varies across the professions, such collaboration to support the early years has proven problematic. This project seeks to address this problem by developing a national interdisciplinary learning and teaching framework to inform higher education curriculum for preparing early years professionals across disciplines. The framework will attend to the diverse demands of multiple professions, qualification levels and workforce agendas. Informed by rigorous scholarship, and optimising interdisciplinary collaboration and engagement, the project design uses multilayered methodologies including modified Delphi rounds, and focus groups.